Septic shock 3.0 in severe COVID19 patients: are we missing something clinically important?. (14th October 2021) - Cidade, J; Morais, R M; Moniz, P M; Costa, V C; Morais, L M; Fidalgo, P F; Brito, S B; Tralhao, A; Paulino, C; Nora, D; Valerio, B; Mendes, V; et al.
Abstract: Introduction/Purpose: COVID19 can be associated with life-threatening organ dysfunction due to septic shock, frequently requiring ICU admission, respiratory and vasopressor support. Therefore, clear clinical criteria are pivotal to early recognition of patients more likely to have poor outcomes, needing prompt organ support. Although most patients with severe COVID19 meet the Sepsis-3.0 criteria for septic shock, it has been increasingly recognized that, in this population, hyperlactatemia is frequently absent, possibly leading to an underestimation of illness severity and mortality risk. Purpose: This study aimed to identify the proportion of patients with COVID19 with hypotension despite adequate volume resuscitation, needing vasopressors to have a MAP>65mmHg, with and without hyperlactatemia, in ICU, and describe its clinical outcomes and mortality rate. Methods: We performed a single-center retrospective cohort study. All adult patients admitted to ICU with COVID19 were eligible and were further divided in 3 groups according to hyperlactatemia (lactate >2mmol/L) and persistent hypotension with vasopressor therapy requirement: (1) sepsis group (without both criteria), (2) vasoplegic shock (with persistent hypotension with vasopressor therapy requirement without hyperlactatemia) and (3) septic shock 3.0 (with both criteria). COVID19 was diagnosed using clinical and radiologic criteria with a SARS-CoV-2 positive RT-PCR test. Qui-square test was used for categorical variables and Kruskal-Wallis and logistic regression were used on continuous variables for statistical assessment of outcomes between groups. Kaplan-Meier survival curve and log-rank test were also obtained. Results: 103 patients (mean age 62 years, 71% males) were included in the analysis (N=45 sepsis, N=25 vasoplegic shock; N=33 septic shock 3.0). SOFA score at ICU admission and ICU length of stay were different between groups (p<0.001). Ventilator-free days and vasopressor-free days were also different between sepsis vs vasoplegic shock and septic shock 3.0 groups (both p<0.001 and p<0.001, respectively), and similar in vasoplegic vs septic shock 3.0 groups (p=0.387 and p=0.193, respectively). Mortality was significantly higher in vasoplegic shock and septic shock 3.0 when compared with sepsis group (p<0.001) without difference between the former two groups (p=0.595). Log rank test of Kaplan-Meier survival curves were also different (p=0.07). Logistic regression identified the maximum dose of vasopressor therapy used (OR 1.065; CI 95%: 1.023–1.108, p=0.02) and serum lactate level (OR 1.543; CI 95%: 1.069–2.23, p=0.02) as the major explanatory variables of mortality rates. Conclusions: In severe COVID19 patients, the Sepsis 3 criteria of septic shock may exclude patients with a similarly high risk of poor outcomes and mortality rate, that should be equally approached. Funding Acknowledgement: Type of funding sources: None.